Keefektifan Bimbingan Kelompok dengan Pendekatan Realitas dalam Meningkatkan Penyesuaian Diri Pada Santri Pondok Pesantren Darun Najah - Regina, Putri; Jannati, Zhila; Janare Putra, Bela (Social Science and Contemporary Issues Journal, 2024)
ABSTRACT:This research is entitled "The Effectiveness of Group Guidance with a Reality Approach in Improving Self-Adjustment in Students at the Darun Najah Islamic Boarding School". The aim of this research is to determine the effectiveness of group guidance using a reality approach in improving student adjustment. This research uses a quantitative approach and this type of research is an experiment with a pre-experimental design. Population of 100 people. From the purposive sampling technique used, a sample of 8 students was obtained. Data collection techniques use documentation, questionnaires and the number of question items is 52 questions from each instrument. After the validation test, the r table is smaller than the calculated r, so the statement is valid. The data normality test used is the Kolmogrov-Smirnov technique, so the pretest and posttest results are normally distributed and the hypothesis test used is the t test with the paired sample test technique. From the t test results there are differences before group guidance was carried out using a reality approach and after a reality approach was carried out. The research results can be seen from the pretest and posttest results where the pretest results are 995 and the posttest results are 1.120 so it can be concluded that the pretest and posttest results increased by a difference of 125 points so group guidance with a reality approach is effective for increasing self-adjustment.